Assessment methods and learning styles for learning satisfaction: the role of self-efficacy - Mahmud, Amir; Susilowati, Nurdian; Sari, Puji Novita (International Journal of Evaluation and Research in Education (IJERE), 2024)
This study aimed to determine the effect of assessment methods and learning styles on online learning satisfaction with self-efficacy as a moderating variable. The study surveyed 228 students from the accounting education major program at a public university in Indonesia. The collected data was analyzed using descriptive statistics and moderation regression analysis (MRA). The results showed that the assessment method and learning styles affected student learning satisfaction. In addition, this study also found that self-efficacy moderated the effect of the assessment method and learning styles on student learning satisfaction. This finding suggests that lecturers can use online assessment methods that are based on student interest so that students can enjoy learning in class and increase the level of satisfaction students can increase. Not only that, but the assessment process will also be a success if the faculty supports every technical source to make online learning run smoothly. Furthermore, when students have self-efficacy when choosing their specific learning style during the assessment process, their satisfaction with online learning will increase. The current study contributes to the existing body of knowledge by stressing that assessment and learning methods are significantly helpful in students’ satisfaction-related self-efficacy.